2020
DOI: 10.1109/jphot.2019.2958311
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Carrier Recombination and Efficiency Droop of AlGaN Deep Ultraviolet Light-Emitting Diodes

Abstract: We investigate temperature-dependent carrier transfer and efficiency droop on AlGaN-based deep ultraviolet light-emitting diodes. The Shockley-Read-Hall (SRH) recombination and carrier leakage are highly associated with the poor thermal stability. The existence of Auger recombination and carrier leakage is identified by the m-power method. A modified ABC model with an additional term f(n) related to carrier leakage is employed to analyze the evolution of multiple recombination mechanisms. The SRH process stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…They emit l high excitation densities, respectively, and thus, parasitic peaks that appe wavelength region can originate from different regions and different type tice defects [73]. The study of these parasitic peaks can determine the qua taxial layer of a device from one side and elucidate the mechanism of ca which provides a reference for the improvement of device epitaxy in the f tion, this group conducted research on the point-defect recombination in Shockley-Read-Hall recombination, trap-assisted recombination), leakage recombination, and other factors that affect the quantum efficiency [74] hand, Kneissl et al inferred that efficiency droop in AlGaN quantum-we tures are caused by an internal carrier loss process, analogous to what occu system. This loss process may be due to Auger recombination, where C = s −1 ; a similar value is commonly observed in InGaN-based devices [75].…”
Section: Carrier Transport and Internal Quantum Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…They emit l high excitation densities, respectively, and thus, parasitic peaks that appe wavelength region can originate from different regions and different type tice defects [73]. The study of these parasitic peaks can determine the qua taxial layer of a device from one side and elucidate the mechanism of ca which provides a reference for the improvement of device epitaxy in the f tion, this group conducted research on the point-defect recombination in Shockley-Read-Hall recombination, trap-assisted recombination), leakage recombination, and other factors that affect the quantum efficiency [74] hand, Kneissl et al inferred that efficiency droop in AlGaN quantum-we tures are caused by an internal carrier loss process, analogous to what occu system. This loss process may be due to Auger recombination, where C = s −1 ; a similar value is commonly observed in InGaN-based devices [75].…”
Section: Carrier Transport and Internal Quantum Efficiencymentioning
confidence: 99%
“…The study of these parasitic peaks can determine the quality of the epitaxial layer of a device from one side and elucidate the mechanism of carrier transport, which provides a reference for the improvement of device epitaxy in the future. In addition, this group conducted research on the point-defect recombination in UV LED (i.e., Shockley-Read-Hall recombination, trap-assisted recombination), leakage current, Auger recombination, and other factors that affect the quantum efficiency [74]. On the other hand, Kneissl et al inferred that efficiency droop in AlGaN quantum-well heterostructures are caused by an internal carrier loss process, analogous to what occurs in an InGaN system.…”
Section: Carrier Transport and Internal Quantum Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [ 25 ] reported a system in which the efficiency droop was approximately 4% at a current density of 110 A cm –2 , despite numerical calculations suggesting that it would almost be free of efficiency droop. Moreover, current droop (J-droop) and temperature droop (T-droop) processes, which are common with visible-light LEDs, are also severe problems in AlGaN-based UVB-LEDs, even for emission wavelengths of less than 280 nm [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. In general, direct transitions between the conduction and valence bands are the key to enhancing the internal quantum efficiencies of multiple quantum wells (MQWs) when developing LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, AlGaN-based LEDs which emit at ultraviolet (UV) wavelengths have begun to mature and have had a notable impact on several fields such as medicine, water purification, sensing and optical communications [1]. The benefit of using deep UV (DUV, UVB 280-315 nm, UVC 100-280 nm) for optical communications is that the ozone layer strongly absorbs most of this region of the electromagnetic spectrum; as a result, terrestrial DUV communications can operate in a low noise environment and can also be used in nonline of sight (NLOS) communications due to the substantial scattering of DUV light in air.…”
Section: Iintroductionmentioning
confidence: 99%